Bar do Orlando e Bar do Nonô : produtos memorialísticos dos bares frente aos projetos de modernidade de Belo Horizonte - Viviane da Silva (2024)
The dissertation aimed to investigate how the memorialistic products of the bars “Bar do Orlando” and “Bar do Nonô” reveal different aspects of Belo Horizonte’s modernity project. We identified how communication highlights or erases memories for the construction of communicational products. Drawing from discussions on modernity by Giddens (1991), Appadurai (2004), and Quijano (2005), as well as discussions on memory and places of memory by Halbwachs (1990), Pollak (1992), and Nora (1993), we selected two memorialistic products for empirical analysis: the audiovisual documentary “Bar do Orlando - 100 anos” [2019] and the book “Nonô - O rei do caldo de mocotó.” We conducted a qualitative-quantitative analysis of these materials. Using Bardin’s (2016) content analysis method and Emerin, Coutinho and Finger (2023) analysis of audiovisual materiality, we developed a methodology that addressed the specificity of the objects. This involved creating an analytical framework with four thematic axes: Narrative Construction, Who Speaks to Us?, Subjects’ Experience with Space, and Photographs and Video, as well as Traces of Tradition, Mineiridade, and Modernity. The results reveal that memory products reflect modernity values, such as family constitution, gender relations, and work relationships, which are intersected by elements of tradition and mineiridade (a term related to the state of Minas Gerais). The emergence of these actors within Belo Horizonte’s modernity landscape highlights the hybrid and diffuse nature of modernity in the city. Additionally, we identified how memories can be manipulated through forgetfulness and erasures to construct a narrative for the official discourse, positioning these bars within the context of Latin American modernity emergence. The project is relevant for discussing the interface between communication and memory in this context.